Task load affects tool embodiment during virtual tool-use in young and older adults - Jahanian-Najafabadi, Amir; Küster, Dennis; Putze, Felix; Godde, Ben (Frontiers in Virtual Reality, 2025)
IntroductionPrior research revealed that after virtual tool use training, younger as compared to older adults, experienced a higher sense of tool-ownership over virtual tools associated with changes in sensorimotor representation (i.e., body schema). Moreover, higher agency ratings over the tool were independent of their performance levels and the extent to which the virtual tool was integrated into their arm representation. In contrast, older adults exhibited an increased sense of agency, which was strongly associated with improvements in virtual tool use performance. Regardless, no changes to their body schema, and no emergence of a sense of ownership were revealed in older adults.MethodsComparing data from a questionnaire and an analogue scale as two subjective measurements of embodiment during and after virtual tool-use training, we investigated whether this tool embodiment in both age groups could be predicted by task load assessed with the NASA TLX where participants rated their perceived task load related to the tool-use task in six dimensions (mental, physical, temporal, effort, performance and frustration). Data from 34 younger and 39 healthy older adults were analyzed.ResultsResults revealed that in younger adults, mental load led to increased ownership ratings over the virtual tool, and physical load negatively affected the sense of agency. Older adults showed weaker effects, with performance load being the only significant predictor of higher agency ratings. Further analyses of the analogue scale, which was embedded as an interactive probe in the experiment, provided novel fine-grained data on perceived sense of control during the training. Our results highlight robust age-related differences in tool-use performance, with younger adults consistently completing tasks more quickly than older adults. Sense of control, captured through the embedded analogue scale, significantly predicted faster performance, whereas ownership ratings did not contribute to timing performance. Agency ratings alone were not predictive, but their relationship with performance varied across age groups, suggesting that different mechanisms may underlie perceived agency in younger and older participants.DiscussionTaken together, these findings indicate that while age strongly influences tool-use efficiency, subjective experiences of control and agency also shape performance, underscoring the value of incorporating multiple measures of embodiment for a comprehensive understanding of virtual tool use.